2016
DOI: 10.1155/2016/3052723
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Transfer and Amide Proton Transfer MRI of Neonatal Brain Development

Abstract: Purpose. This study aims to evaluate the process of brain development in neonates using combined amide proton transfer (APT) imaging and conventional magnetization transfer (MT) imaging. Materials and Methods. Case data were reviewed for all patients hospitalized in our institution's neonatal ward. Patients underwent APT and MT imaging (a single protocol) immediately following the routine MR examination. Single-slice APT/MT axial imaging was performed at the level of the basal ganglia. APT and MT ratio (MTR) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is still far from clinical applications; however, some promising results in neonates are available. In particular, Zheng et al demonstrated that protein content in the WM of neonates measured by amide proton transfer (APT) imaging correlates with age and could provide valuable data about brain maturation at the molecular level (Zheng et al, 2016).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…It is still far from clinical applications; however, some promising results in neonates are available. In particular, Zheng et al demonstrated that protein content in the WM of neonates measured by amide proton transfer (APT) imaging correlates with age and could provide valuable data about brain maturation at the molecular level (Zheng et al, 2016).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…First proposed by Zhou et al, APT imaging is a relatively nascent imaging approach that draws upon CEST and MT imaging propositions. [31][32][33] APT sequence typically incorporates a long saturation pulse (0.5-2 seconds; to saturate more water protons) and an ensuing image acquisition component (usually 2D/3D; gradient echo/spin echo/echo planar imaging). APT imaging contrast is based on a non-invasive in vivo assessment of spin exchange between the tissue bulk water and amide protons of mobile endogenous proteins and peptides chains (which have their signature resonance frequency at 3.5 ppm downfield that of water in the Z spectrum).…”
Section: Discussionmentioning
confidence: 99%
“…Lately, this modality has shown promise in glioma evaluation [34][35][36] and assessment of brain maturation. 33,37 Brain maturation and myelination have seen an exponential decrease in the APTw signal (white matter > grey matter), reaching up to 0.18 (fitted MTR at 3.5 ppm) in the putamen and 0.87 (fitted MTR at 3.5 ppm) in the frontal white matter, with no significant changes in the latter part of the first decade. 37 Proteomic profiles of the gliomas have been shown to vary considerably according to their WHO grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amide proton transfer imaging (APT) contrast, a type of CEST, detects cellular mobile proteins and peptides. Semi-solid magnetization transfer contrast (MTC) quantifies the number of macromolecular substances, such as structural proteins and carbohydrates (13)(14)(15). Increased metabolites and varied metabolism typically accompany the rapid growth of gliomas.…”
Section: Introductionmentioning
confidence: 99%